Compulsory license to exploit the patent In Algerian law - MERMOUN, Moussa (Journal of Human Sciences, 2020)
Intellectual Property Protection is one of the Most Sensitive Areas, Because it Regulates the Rithts Associated with the Human Creative Achievements, all Legislation has Estabilished legal Systems for the Protection of Intellectual Property Rights in its two Categories, Literary Andartistic Property Rights - Copyright, Related Rights and Industrial Property Rights.the legal System for the Protection of Inventions is an Important Aspect of Industrial Property, il is an Importantbasis for Industrial Development of the Economic Policy of the state, the Systam is Represented in the Patent Granted to the Inventor in Accordance with the Conditions and Procedures Stipulated by the law, and one of the mot Impoant Implications of its Issuance, is the Righe of its Owner to Monopolize the Explotation of the Invention while Proventing others from doing this Exploitation Without his Approval or Authorization.